Determinants of infants and young children feeding practices among mothers living in Saudi Arabia: a cross-sectional study - Fatimah Alsada; Tunny Sebastian; Zainab Alzayer; Hawraa Alabbas; Narjis Alhaddad; Hawraa Abu Shahin; Atheer Alghamdi; Haya F. Alhmly; Malek J. Baassiri; Bedour Alkhalifa; Antonina N. Mutoro; Wesam A. Alyahya (BMC Public Health)
Abstract Background The WHO sets evidence-based guidelines for infant feeding. Adhering to the WHO guidelines ensures that infants receive the proper nutrition and thus is associated with healthy growth and development. Aim To describe breastfeeding and complementary feeding practices (CFPs) for infants and young children and identify determinants of appropriate feeding practices. Methods This cross-sectional study was performed via structured interviews with mothers living in Saudi Arabia’s Eastern Province who had children aged 6–24 months. To evaluate their adherence to the recommended WHO practices, a scoring method was applied (0–9). Results 395 mothers were interviewed. The rate of breastfeeding within the first hour, and exclusively breastfeeding for six months was both 25%. Multivariate analysis showed that exclusive breastfeeding for at least six months was less likely in middle-income mothers were less likely to exclusively breastfeed for six months than high-income mothers (OR = 0.32; 95% CI: 0.18–0.57; p < 0.001). Mothers without domestic help were also less likely to exclusively breastfeed (OR = 3.0; p < 0.001), as were those not living with their husbands (OR = 2.1; p = 0.007). Multiparous mothers and those with higher education were more likely to breastfeed than high school graduates (OR = 2.3, p = 0.02; OR = 4.4, p = 0.015, respectively). Timely breastfeeding initiation within the first hour was more common in term infants than preterm infants (OR = 5.3; p = 0.033), and infants born through normal delivery were four times more likely to initiate breastfeeding early (OR = 4.0; p < 0.001). For CFPs, 42% of participants introduced solid food at six months. 55% of mothers reported poor CFPs, primarily due to inappropriate timing of solid food introduction, choking hazards, and delayed introduction of family meals. Good CFPs were positively associated with higher maternal education, increased income, and living with a husband. Conclusion Partial compliance with WHO CFP standards need improvement. Interventions should raise awareness of factors leading to poor compliance and support early breastfeeding initiation and continuation. Low-income and less educated families appear to be most in need of support.